Introduction to the concept of “welfare potential” of production systems and its practical relevance to welfare labelling - Murphy, Eimear; Legrand, Amélie (Frontiers in Animal Science, 2023)
Farm animal welfare is inextricably linked to, and limited by, the welfare potential of the production system. Welfare potential is determined by the method of production, with key housing features and the genetics of the animal being the primary defining factors. Housing systems with close confinement, or using animals selected for productivity to the detriment of welfare, such as fast-growing broilers, cannot deliver good welfare as the causes of poor welfare are an inherent part of the system. Good management, while not a determinant of the welfare potential, is essential for a system to achieve its potential. Viewing systems in terms of their welfare potential reduces the risk of making ongoing incremental changes to systems where welfare can never be high. It sets a framework for evaluating the inputs into a system which are key to ensure an acceptable level of welfare. This approach has practical relevance for certification schemes, as it allows for a tiered (“bad, better, best”) approach to food labelling based on method of production (e.g. intensive indoors, higher welfare indoors, free-range). Paired with robust welfare outcomes assessment and auditing, this can provide clear and simple information on the farming system to the consumers, while ensuring that the system delivers good welfare. There is an urgent need to move away from systems with a low welfare potential, as they can never deliver acceptable levels of welfare, and to support farmers in their transition towards systems with a higher welfare potential.